Significant loss of Bone and Skin- Muscle Post Traumatic of Elbow: Support Strategy in a Developing Country - James Yaovi Edem; Komla Sena Amouzou; Messanvi Yao Akpoto; Assang Dossim (Journal of Surgery and Surgical Research - Peertechz Publications, 2017)
Purpose: The elbow bone traumas are very serious lesions that can compromise the function of this joint in the future. These lesions are most severe when there is a defect of bone which affects one component of the joint. Case report: We report a case of open trauma of the left elbow from a right-handed girl of 21 years, during an accident on the highway. On admission, the victim had a signifi cant defect of skin-muscle of the anterior medial aspect of the elbow. The exploration revealed a major loss of bone affecting the humeral trochlea which was completely absent. In emergency the patient has benefi ted from joint stabilization by an external fi xation, with a fi lling-in of the humeral-ulnar joint space with a cement spacer. The loss of muscle substance was fi lled with a latissimus dorsi fl ap followed by a skin graft made the days that followed. Conclusion: After a brief review of the literature, the authors emphasize on the need to preserve the joint space through the establishment of the spacer which is the only guarantee for maintaining the stability of the elbow, which also allows to consider arthroplasty surgery later.